Flavonoids' Effects on Caenorhabditis elegans' Longevity, Fat Accumulation, Stress Resistance and Gene Modulation Involve mTOR, SKN-1 and DAF-16 - María Alejandra Guerrero-Rubio; Samanta Hernández-García; Francisco García-Carmona; Fernando Gandía-Herrero (MDPI AG, 2021)
Flavonoids are potential nutraceutical compounds present in diary food. They are considered health-promoting compounds and promising drugs for different diseases, such as neurological and inflammatory diseases, diabetes and cancer. Therefore, toxicological and mechanistic studies should be done to assert the biological effects and identify the molecular targets of these compounds. In this work we describe the effects of six structurally-related flavonoids-baicalein, chrysin, scutellarein, 6-hydroxyflavone, 6,7-dihydroxyflavone and 7,8-dihydroxyflavone-on Caenorhabditis elegans' lifespan and stress resistance. The results showed that chrysin, 6-hydroxyflavone and baicalein prolonged C. elegans' lifespan by up to 8.5%, 11.8% and 18.6%, respectively. The lifespan extensions caused by these flavonoids are dependent on different signaling pathways. The results suggested that chrysin's effects are dependent on the insulin signaling pathway via DAF-16/FOXO. Baicalein and 6-hydroxyflavone's effects are dependent on the SKN-1/Nfr2 pathway. In addition, microarray analysis showed that baicalein downregulates important age-related genes, such as mTOR and PARP.